2018
DOI: 10.1002/hon.2512
|View full text |Cite
|
Sign up to set email alerts
|

Refractory diffuse large B‐cell lymphoma after first‐line immuno‐CT: Treatment options and outcomes

Abstract: In the rituximab era, one-third of diffuse large B-cell lymphoma patients experience relapse/refractory disease after first-line anthracycline-based immunochemotherapy. Optimal management remains an unmet medical need. The aim of this study was to report the outcomes of a cohort of refractory patients according to their patterns of refractoriness and the type of salvage option. We performed a retrospective analysis, which included 104 diffuse large B-cell lymphoma patients treated at Lyon Sud University Hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…2 Refractory/relapsed (R/R) patients usually have a very poor outcome. [3][4][5] Initially approved for R/R acute lymphoblastic leukemia (ALL) in pediatric and young adult patients in April 2017 in the USA, 6,7 tisa-cel was subsequently approved for the treatment of R/R DLBCL and transformed follicular lymphoma (trFL) after 2 or more lines of systemic therapy in August 2018 in Europe. Likewise, axi-cel was approved in August 2018 for R/R DLBCL, trFL and primary mediastinal B cell lymphoma (PMBCL) after two or more lines of systemic therapy in Europe.…”
Section: Indroductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Refractory/relapsed (R/R) patients usually have a very poor outcome. [3][4][5] Initially approved for R/R acute lymphoblastic leukemia (ALL) in pediatric and young adult patients in April 2017 in the USA, 6,7 tisa-cel was subsequently approved for the treatment of R/R DLBCL and transformed follicular lymphoma (trFL) after 2 or more lines of systemic therapy in August 2018 in Europe. Likewise, axi-cel was approved in August 2018 for R/R DLBCL, trFL and primary mediastinal B cell lymphoma (PMBCL) after two or more lines of systemic therapy in Europe.…”
Section: Indroductionmentioning
confidence: 99%
“…Although the majority of patients are cured with first‐line immunochemotherapy, 10% to 15% have primary refractory disease, and another 20% to 35% ultimately experience relapse 2 . Refractory/relapsed (R/R) patients usually have a very poor outcome 3‐5 …”
Section: Indroductionmentioning
confidence: 99%
“…Age-adjusted IPI (aaIPI), a derivative of the IPI score based on lactate dehydrogenase (LDH), stage, and ECOG performance status, can stratify the patients at diagnosis and predicts outcome (3). In patients older than 60 years, DLBCL can be cured in 50% to 60% of the cases following first-line R-CHOP (4-6) and 30% to 40% will present a R-CHOP primary refractory or an early-relapse disease (7,8). Those "poor responders" to R-CHOP have a 1-year overall survival (OS) of less than 20% and still represent a group of patients with a clear unmet medical need (7).…”
Section: Introductionmentioning
confidence: 99%
“…The response was evaluated by CT. 4 Responses to second line in a French retrospective study with 104 patients were CR 23%, with 77% patients receiving Rituximab in salvage regimens. 13 The NCIC-CTG LY.12 study showed a CR of 13.8% for GDP and 14.6% for DHAP in a population with 71% primary refractory or relapsed within 1 year. In this study, the response was also evaluated by CT. 5 Compared to these results, our patients achieved slightly higher rates of response to second line treatment.…”
Section: Discussionmentioning
confidence: 98%